The implementation of Markov chain to predict market share smartphone customers in Surabaya during pandemic COVID-19 / Hilyatun Nuha ... [et al.] - Nuha, Hilyatun; Widiasih, Wiwin; Romadon, Mustofa Wahyu (Universiti Teknologi MARA, Kedah, 2022)
In the second quarter of 2019, smartphone shipments in Indonesia reached the highest figure in history, which was 9.7 million units according to a market research Indonesia Digital Conference (IDC). The smartphone competition in Indonesia continues to increase drastically in 2018. Samsung survived on the top position with a market share of 25.4% followed by Xiaomi 20.5%, Oppo 19.5% and Vivo 15.9%. The four smartphone brands are the biggest market share smartphone in Indonesia. In this summary, this research will propose market share prediction for each smartphone brand in Surabaya up to 2023 using Markov Chain. This research will identify factors in the selection of smartphone brands. Then we will determine the weight of each factor using Analytical Hierarchy process (AHP). Finding the right marketing strategy with the expectation that smartphone vendor can maintain and increase the volume of sales of its products so that it can reach the desired market share. The purpose of this research is to be able to provide suggestion for smartphone businesses in Surabaya.